Promiscuity resolves constraints on social mate choice imposed by population viscosity - Geoffrey M. While; Tobias Uller; Genevieve Bordogna; Erik Wapstra (Molecular Ecology, 2014)
Population viscosity can have major consequences for adaptive evolution, in particular for phenotypes involved in social interactions. For example, population viscosity increases the probability of mating with close kin, resulting in selection for mechanisms that circumvent the potential negative consequences of inbreeding. Female promiscuity is often suggested to be one such mechanism. However, whether avoidance of genetically similar partners is a major selective force shaping patterns of promiscuity remains poorly supported by empirical data. Here, we show (i) that fine‐scale genetic structure constrains social mate choice in a pair‐bonding lizard, resulting in individuals pairing with genetically similar individuals, (ii) that these constraints are circumvented by multiple mating with less related individuals and (iii) that this results in increased heterozygosity of offspring. Despite this, we did not detect any significant effects of heterozygosity on offspring or adult fitness or a strong relationship between pair relatedness and female multiple mating. We discuss these results within the context of incorporating the genetic context dependence of mating strategies into a holistic understanding of mating system evolution.